Rapid synthesis under mild conditions of an acrylic diamide N, N, N, N'T etrabutylphthalamide, a potential antimicrobial agent - Abrenica, Graniel Harne A.; Bernardo, Valeree Ross R.; Paredes, Fiona U.; Arco, Susan D. (2011)
The amide functional group is a common feature in both small and complex synthetic or natural molecules. It is one of the most significant functional groups of organic molecules in terms of medicinal use. Medicinal Chemistry database showed that approximately 25% of known drugs contain this carboxamide group. The synthesis of acyclic diamide, N, N, N', N'tetrabutylphthalamide, by the condensation with phthalic anhydride in dioxane of dibutylamine proved to be highly efficient. A product yield of 85% was obtained under mild conditions (6-hour reaction time at 27ÚC). The product was recrystallized in acetonitrile. The successful synthesis was confirmed through spectroscopic techniques such as infrared, nuclear magnetic resonance and mass spectroscopy. The purified product was tested for antimicrobial activity against Escherichia coli, Staphylococcus aureus, Candida albicans and Aspergillus niger. Chlorampenicol and clotrimazole were used as positive controls. The acyclic diamide exhibited antimicrobial activity with an antimicrobial index of 0.1 against Escherichia coli, 0.3 against Staphylococcus aureus and 0.2 against Candida albicans. No inhibition activity against Aspergillus niger was observed.
Keywords: Butterflies; Dividivi (Tree); University of the Philippines (Los Baños)